The European Union - Watts, Duncan (Edinburgh University Press, 2008)
The European Union is one of the world?s most complex political systems: this makes it a challenge to study. To the uninitiated its institutions seem remote, its remit unclear, its operations difficult to understand and its outputs sometimes perplexing. It combines some attributes of a state with those of an international organisation, yet it closely resembles neither. Its development is shaped by an increasing number of players, including 25 member governments, multiple common EU institutions, clusters of experts, private interests and citizen groups. All converge to influence what the EU is.